Efikasi Minyak Atsiri Sereh Dapur (Cymbopogon citratus L.) terhadap Hama Ulat Daun Kubis (plutella xylostella L.) di Laboratorium - HENDRA DWI PRASETYO; I WAYAN SUSILA; KETUT SUMIARTHA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2013)
ABSTRACT Efficacy of Essential Oil of Lemongrass (Cymbopogon citratus L.) to Diamond Back Moth (Plutella xylostella L.) on Cabbage in the Laboratory The use of synthetic pesticides continuously will be affect the biotic and non-biotic factors. Therefore, the others control measure which were practically, effectively and safely to human being and environmental - frendly must be created. Geographic condition of Indonesian has been known is rich in biodiversity is necessary to be studied to find the sources for pest control measure which is environmental-friendly. Study about “ Efficacy of Essential oil of Lemongrass (Cymbopogon citratus L.) to Diamond Back Moth (Plutella xylostella L.) on Cabbage was conducted in February, 4. to October, 18.2012 in the Laboratory of Pest and Diseases, Departement of Agroekotechnology, Faculty of Agriculture, Udayana University. The purpose of this study is to determine killing capacity of essential oil of Lemongrass (C. citratus) against Diamond Back Moth (P. xylostella) on Cabbage. The results showed that the essential oil of Lemongrass is effective to kill the larvae of DBM (P. xylostella). The level of concentrations that is used as treatment in this study are 1.5%, 1.25%, 1.%, 0.75%, and 0.5% that have a significant effect to kill the larvae of P. xylostella compare to the control treatment (tween 80 and water). Concretation 0.5% of lemongrass oil causing mortality in average 38.67%, while the concentrations 1.5% is 100%. The concretations 1.25%, 1%, and 0.75% their percentage of mortality are 94.67%, 74.67%, and 56%, respectively. Base on the results of this study, the optimum concretation which are give mortality to the larvae is 1,5% with the percentage of mortality reach to 100% on 6 days after treatment. Key words: Efficacy, Lemongrass (Cymbopogon citratus), Diamond Back Moth (Plutella xylostella)